Evaluation of lower-body gait kinematics on outdoor surfaces using wearable sensors - Shah, Vaibhav R.; Dixon, Phillipe C.; Willmott, Alexander P. (Journal of biomechanics, 2024)
The effects of outdoor surfaces on gait are unclear due to difficulties associated with motion tracking outside laboratories. Today, inertial measurement unit (IMU) systems can be deployed to understand the biomechanical adaptations required to navigate real-world environments successfully. This study used IMUs devices to identify lower-limb kinematic adaptations while walking on outdoor surfaces. We hypothesize that gait adaptations between surface types will present as differences in lower-limb joint angles. Thirty able-bodied adults performed walking trials with IMUs on the lower back, thighs, and shanks. Outdoor walking surfaces were flat and even (flateven) (0° grade cement), cobblestone, grass, slope up, slope down, stairs up, and stairs down. A complementary-based sensor fusion algorithm was used to compute hip and knee joint flexion–extension angles, and data were normalized to 100 % of the gait cycle based on foot-strike events. Flateven walking was compared against all other surfaces. Two-sample one-dimensional statistical parametric mapping (1d-SPM) t-tests were used to identify differences between angles (α ≤ 0.05). Significant differences in joint angles were identified when grass, slope up, slope down, stairs up, and stairs down walking were compared with flateven (p ≤ 0.005). Moreover, differences were found between slope and stair conditions (p ≤ 0.004). No significant differences were noted between flateven and cobblestone. This study demonstrates that gait adaptations driven by differences in surface types can be observed using IMU sensors in an outdoor setting.